The Influence of Balanced Nutrition Education on The Knowledge of Posyandu Cadres in Preventing Stunting - Maria Vilastry Nuhan; Damita Palalangan; Yosefa S.Atok; Christina R.Nenotek (STIKes Patria Husada Blitar, 2023)
Childhood stunting, a persistent public health concern in Indonesia, has significant implications for long-term health. Improving the knowledge of balanced nutrition among Posyandu cadres plays a pivotal role in tackling this issue. Our objective was to assess the impact of balanced nutrition education on Posyandu cadre knowledge concerning stunting prevention. The research involved 129 participants and evaluated their knowledge through pretest and posttest scores, employing the Wilcoxon Sign Rank Test for statistical analysis. The results indicated that the majority of respondents initially possessed